Determinants of serum concentrations of organochlorine compounds in Swedish pregnant women: a cross-sectional study - Cnattingius Sven; Darnerud Per; Aune Marie; Glynn Anders; Bjerselius Rickard; Becker Wulf; Lignell Sanna (Environmental Health, 2007)
Abstract Background We performed a cross-sectional study of associations between personal characteristics and lipid-adjusted serum concentrations of certain PCB congeners and chlorinated pesticides/metabolites among 323 pregnant primiparous women from Uppsala County (age 18–41 years) sampled 1996–1999. Methods Extensive personal interviews and questionnaires about personal characteristics were performed both during and after pregnancy. Concentrations of organochlorine compounds in serum lipids in late pregnancy were analysed by gas chromatography. Associations between personal characteristics and serum levels of organochlorine compounds were analysed by multiple linear regression. Results Participation rate was 82% (325 of 395 women). Serum concentrations of PCB congeners IUPAC no. 28, 52, 101, 105 and 167, and o, p'-DDT and -DDE, p, p'-DDT and -DDD, oxychlordane, and γ- and α-HCH were in many cases below the limit of quantification (LOQ). No statistical analysis of associations with personal characteristics could be performed for these substances. Concentrations of PCB congeners IUPAC no. 118, 138, 153, 156 and 180, HCB, β-HCH, trans-nonachlor and p, p'-DDE increased with increased age and were highest in women sampled early during the 4 year study period. This shows that older women and women sampled early in the study had experienced the highest life-time exposure levels, probably mainly during childhood and adolescence. The importance of early exposures was supported by lower PCB concentrations and higher β-HCH and p, p'-DDE concentrations among women born in non-Nordic countries. Moreover, serum concentrations of certain PCBs and pesticide/metabolites were positively associated with consumption of fatty fish during adolescence, and concentrations of CB 156, CB 180 and p, p'-DDE increased significantly with number of months women had been breast-fed during infancy. Short-term changes in bodily constitution may, however, also influence serum concentrations, as suggested by negative associations between concentrations of organochlorine compounds and BMI before pregnancy and weight change during pregnancy. Conclusion Although some of the associations could be caused by unknown personal characteristics confounding the results, our findings suggest that exposures to organochlorine compounds during childhood and adolescence influence the body burdens of the compounds during pregnancy.